PEMBERDAYAAN MASYARAKAT KAMPUNG SDGs SUKOREJO, JEMBER MELALUI PEMANFAATAN DAN PENGOLAHAN TANAMAN OBAT - Nuri Nuri (LPPM Universitas dr. Soebandi, 2026)
This article reports a community engagement program aimed at empowering local communities in the SDGs Village of Sukorejo, Bangsalsari District, Jember Regency, Indonesia, through the utilization and processing of medicinal plants. Despite Indonesia’s rich biodiversity and significant potential for traditional medicine development, community knowledge regarding proper identification, cultivation, and processing of medicinal plants remains limited. This program was designed to enhance community capacity by improving knowledge and technical skills, while simultaneously exploring the economic potential of locally available medicinal resources. A participatory approach was employed, consisting of comprehensive health education, hands-on training in the preparation of simplisia (dried medicinal raw materials), and continuous mentoring. The results demonstrated a substantial improvement in participants’ knowledge and practical competencies. The independent use of medicinal plants contributed to improved household health practices, while the development of value-added herbal products created new income-generating opportunities. Importantly, this program aligns with and directly supports the achievement of Village Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being) and SDG 8 (Decent Work and Economic Growth), by fostering community-based health resilience and local economic empowerment. This model highlights a scalable and sustainable strategy for integrating traditional knowledge with community development initiatives in rural settings.